ANALYSIS OF COASTAL AREA MANAGEMENT THROUGH A COMMUNITY-BASED APPROACH IN PESAWARAN DISTRICT - Nugraheni, Irma Lusi; Eka Y R, Riyantika; Pratiwi, Dinar (Jurnal Segara, 2024)
Pesawaran Regency is a buffer zone for the capital city of Lampung Province which has a fairly wide and potential coastal area. With a variety of rich biodiversity and environmental services provided, coastal and marine resources have high economic and ecological value. In order to ensure the sustainability of these resources, their management must be carried out in a planned and integrated manner and be able to provide the maximum benefit to all stakeholders, especially coastal communities, and minimize impacts and conflicts that could potentially occur. The method used in this study is literature study. The results show that coastal communities in Pesawaran Regency have a fairly active role in the management of coastal areas.